When Unequals Compete: Where Do They Stand After the Competition?. Issue 1 (23rd January 2022) - Hart, Einav; Avrahami, Judith; Kareev, Yaakov
Abstract: When two unequals compete, the stronger, more able, richer competitor commonly stands a better chance of winning. If the stronger competitor does win, this worsens the relative status of the weaker competitor even further. Does this result depend on the type of competition? Does it depend on the size of the reward to be won? In the present paper, we report an experimental study of how a very simple competitive mechanism can affect the relative standing of the weaker, poorer of two competitors. In a lab experiment with 208 participants, we employed competitions with different levels of uncertainty in how a winner was determined and with different sizes of rewards to be won, to explore effects on the relative standing of the weaker and stronger competitors. We used an investment game in which participants differing in their endowed budgets competed against one another, forfeiting their investment whether they won or lost. Two versions of the game were used: a simple all‐pay‐auction contest and a non‐constant‐sum Colonel Blotto contest (Roberson & Kvasov, 2012), both with players that were unequal in their budgets. Results revealed that, in line with published game‐theoretic solutions, the relative standing of the weaker agents worsened following competition, and increasingly so the higher the rewards. At the same time, the effect was mitigated in the variant of the Colonel Blotto game, which involved more uncertainty in how the winner was determined.